2015
DOI: 10.1016/j.expthermflusci.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

A simultaneous planar laser-induced fluorescence, particle image velocimetry and particle tracking velocimetry technique for the investigation of thin liquid-film flows

Abstract: A simultaneous measurement technique based on planar laser-induced fluorescence imaging (PLIF) and particle image/tracking velocimetry (PIV/PTV) is described for the investigation of the hydrodynamic characteristics of harmonically excited liquid thin-film flows. The technique is applied as part of an extensive experimental campaign that covers four different Kapitza (Ka) number liquids, Reynolds (Re) numbers spanning the range 2.3 -320, and inlet-forced/wave frequencies in the range 1 -10 Hz. Film thicknesses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
79
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 113 publications
(86 citation statements)
references
References 56 publications
7
79
0
Order By: Relevance
“…Note that the velocity profile is parabolic in the tail and underneath the crest of the solitary wave, even for the case with the highest Reynolds number (case C6, Re = 77). This agrees with previously reported numerical results (Malamataris et al 2002;Gao et al 2003;Malamataris & Balakotaiah 2008) and experimental measurements (Adomeit & Renz 2000;Moran et al 2002;Charogiannis et al 2015). Interestingly, the self-similarity of the velocity profile in the laboratory frame of reference is unaffected by the onset of a recirculation region in the moving frame when the maximum flow velocity exceeds the wave speed (for instance, in case C6).…”
Section: Comparison Of Experimental and Numerical Resultssupporting
confidence: 81%
“…Note that the velocity profile is parabolic in the tail and underneath the crest of the solitary wave, even for the case with the highest Reynolds number (case C6, Re = 77). This agrees with previously reported numerical results (Malamataris et al 2002;Gao et al 2003;Malamataris & Balakotaiah 2008) and experimental measurements (Adomeit & Renz 2000;Moran et al 2002;Charogiannis et al 2015). Interestingly, the self-similarity of the velocity profile in the laboratory frame of reference is unaffected by the onset of a recirculation region in the moving frame when the maximum flow velocity exceeds the wave speed (for instance, in case C6).…”
Section: Comparison Of Experimental and Numerical Resultssupporting
confidence: 81%
“…In a previous study on the dynamics of solitary waves on inertia-dominated falling liquid film of Denner et al [37], the results obtained with the DNS framework [47][48][49] used in this study showed excellent agreement with experimental measurements [6]. We propose a novel scaling for solitary waves, which we derive from the Nusselt flat film solution based on the physical mechanisms that underpin the growth and dispersion of solitary waves.…”
Section: Introductionmentioning
confidence: 63%
“…This leads to a strongly non-parabolic velocity profile at the front of the solitary wave [6,36,37], including flow reversal underneath the trough preceding the solitary wave under certain conditions [4,5,38,39]. Furthermore, if inertia is sufficiently high, the maximum flow velocity of the film exceeds the phase velocity of the solitary waves, leading to a recirculation zone in the main wave hump with respect to the reference frame moving with the wave [39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations